EFFECT OF ALPHA TOCOPHEROL SUPPLEMENTATION ON FGF EXPRESSION IN HUMAN BONE MARROW MESENCHYMAL STEM CELLS (IN VITRO STUDY) - Reza Al Fessi, - (Global Science Publications, 2018)
In tissue engineering, the administration of alpha tocopherol is reported to increase wound healing, given the possibility of a lack of microcirculation in the graft area. Alpha tocopherol is also known to increase the proliferation of mesenchymal stem cells, induce osteoblast differentiation, and increase the formation of collagen fibers. This study aims to determine the effect of additionAlpha tocopherol on FGF expression on bone marrow mesenchymal stem cell cultures. Culture samples taken from Bone marrow aspiration from adult human femur bones. To get the homogeneity of the research data, the researcher uses as many as 5 samples for each treatment. The expressions of FGF was then evaluated using immunocytochemistry on the 1st, 3rd and 7th day. The collected data was then analyzed using comparative analysis test. The results showed that there was no significant difference in FGF expression in hBM-MSC by addition of alpha tocopherol supplementation compared with control. Addition of Alpha tocopherol supplementation does not influence of FGF expression on bone marrow masenchymal stem cell.